The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/19458924211009429
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II, Multicenter, Randomized, Placebo-Controlled Study of Benralizumab, a Humanized Anti-IL-5R Alpha Monoclonal Antibody, in Patients With Eosinophilic Chronic Rhinosinusitis

Abstract: Background Strong eosinophil infiltration in chronic rhinosinusitis with nasal polyp (CRSwNP) is highly associated with recalcitrance and higher nasal polyp recurrence rate after surgery. The prevalence of eosinophilic CRSwNP (ECRS) is increasing in Asian countries including Japan. Benralizumab is a humanized anti-IL-5R alpha monoclonal antibody that depletes eosinophils by antibody-dependent cell-mediated cytotoxicity. Objective To assess the efficacy and safety of benralizumab in patients with ECRS. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 30 publications
0
33
0
1
Order By: Relevance
“…Peripheral eosinophil count is associated with tissue eosinophilia in CRSwNP and has been proposed as a surrogate marker thereof. 33 Reductions in NPS with benralizumab have previously been linked to baseline blood eosinophil count in patients with CRSwNP, 23,34 and eosinophils in sinonasal mucosa and peripheral blood are elevated to a greater degree in patients with CRS and asthma than in patients with CRS alone. [35][36][37] In OSTRO, patients with comorbid asthma had higher mean baseline blood eosinophil counts than patients without the disease (Table E1).…”
Section: Discussionmentioning
confidence: 97%
“…Peripheral eosinophil count is associated with tissue eosinophilia in CRSwNP and has been proposed as a surrogate marker thereof. 33 Reductions in NPS with benralizumab have previously been linked to baseline blood eosinophil count in patients with CRSwNP, 23,34 and eosinophils in sinonasal mucosa and peripheral blood are elevated to a greater degree in patients with CRS and asthma than in patients with CRS alone. [35][36][37] In OSTRO, patients with comorbid asthma had higher mean baseline blood eosinophil counts than patients without the disease (Table E1).…”
Section: Discussionmentioning
confidence: 97%
“…72 Therefore, the results cannot be extrapolated to the general Asian population. Recently, Takabayashi et al 73 conducted a phase 2 study on the effects of benralizumab, a humanized anti-IL-5Rα monoclonal antibody, on Japanese patients with eosinophilic chronic rhinosinusitis, 73 and found that although benralizumab did not meet the primary efficacy endpoint, patients with high blood eosinophil levels had a greater tendency to respond to benralizumab treatment. This finding further reinforces the endotype depend- Although the percentage of recurrence in CRSsNP patients is remarkably lower than that described in CRSwNP patients, approximately 12.9% of CRSsNP patients may recur within 12 years, and CRSsNP patients with T2 inflammation have higher recurrence rates.…”
Section: Current Evidence Regarding T2 Biologics In Asian Crswnp Pati...mentioning
confidence: 99%
“…202 It also has a specific license from the EMA, for patients with severe T2 asthma who have co-existent severe eczema or CRSwNP. 202 Similarly, anti-IL-5 and IL-5R drugs, following successful clinical trials, are also currently under assessment for approval by multiple regulatory bodies for use in other eosinophilic conditions such as Eosinophilic Granulomatosis with Polyangiitis, 248,274 CRSwNP [275][276][277] and Eosinophilic oesophagitis. 278 Mepolizumab specifically has been approved by the Food and Drug Administration for Eosinophilic Granulomatosis with Polyangiitis 278 Finally, Omalizumab is also licensed for use in treatment-resistant chronic spontaneous urticaria and CRSwNP.…”
Section: Monoclonal Antibody Selection For Asthma and Comorbiditiesmentioning
confidence: 99%